Effect of Resistance Training Methods and Intensity on the Adolescent Swimmer's Performance: A Systematic Review - Guo, Wei; Soh, Kim Geok; Zakaria, Noor Syamilah; Hidayat Baharuldin, Mohamad Taufik; Gao, Yongqi (Frontiers in Public Health, 2022)
Background：Resistance training has been widely used in various sports and improves competition performance, especially in swimming. Swimming performance is highly dependent on muscle strength, especially short distances. The driving force of swimming mainly comes from the power of the upper, lower limbs, and torso. There is a strong correlation between strength and swimming performance. For adolescent athletes, the existing literature has bound to prove that resistance training is undoubtedly bound to improve adolescent swimmers' performance. The research mainly focuses on 50-meter and 100-meter swimming performance. Objectives: This study adopts a systematic literature review to (1) examine the effects of resistance training on the performance of adolescent swimmers, and (2) summarise their training methods and intensity. Methods: Electronic databases using various keywords related to “resistance training” and “adolescent swimmers” were searched. Sixteen studies met the inclusion and exclusion criteria where the data was then systematically reviewed using the PRISMA guideline. Furthermore, the physical therapy evidence database (PEDro) scale was used to measure each study’s scientific rigour. Results: This review found that to improve the swimming performance of adolescents, two types of resistance training were used, specifically in water and on land, where both types of training can improve swimming performance. In addition, training with two types of resistance machines were better in the water than with one equipment. Resistance training can improve the swimming performance of adolescent swimmers at 50m, 100m, 200m and 400m distances. However, most studies only focused on the swimming performance at 50m and 100m lengths. A low-intensity, high-speed resistance training programme is recommended for adolescent swimmers to obtain the best training results. Conclusion: Water or land resistance training can improve the swimming performance, especially for 50m and 100m events. Given that both types of exercises have their strengths and weaknesses, combining these methods may enhance the swimmers’ performance. In addition, despite the starting and turning phases consuming up to one-third of the total swimming time for short distances, literature in this area is limited.